2016
DOI: 10.1007/s11663-016-0697-7
|View full text |Cite
|
Sign up to set email alerts
|

Control of Crystal Morphology for Mold Flux During High-Aluminum AHSS Continuous Casting Process

Abstract: In the present manuscript, the efforts to control the crystal morphology are carried out aiming at improving the lubrication of lime-alumina-based mold flux for casting advanced high-strength steel with high aluminum. Jackson a factors for crystals of melt crystallization in multi-component mold fluxes are established and reasonably evaluated by applying thermodynamic databases to understand the crystal morphology control both in lime-alumina-based and lime-silica-based mold fluxes. The results show that Jacks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…The SEM observations showed the primary crystalline phases in the slag were faceted morphology, 16) indicating that the crystallization of the crystalline phase is controlled by interfacial reaction. 35,36) It can be concluded that the crystallization of primary crystalline phase (11CaO•7Al 2 O 3 •CaF 2 ) in the 37) but different from the findings that the crystallization of slag is controlled by element diffusion. [38][39][40] Figure 6 shows the room temperature Raman spectra of the glassy samples with varying TiO 2 contents.…”
Section: Samplementioning
confidence: 72%
“…The SEM observations showed the primary crystalline phases in the slag were faceted morphology, 16) indicating that the crystallization of the crystalline phase is controlled by interfacial reaction. 35,36) It can be concluded that the crystallization of primary crystalline phase (11CaO•7Al 2 O 3 •CaF 2 ) in the 37) but different from the findings that the crystallization of slag is controlled by element diffusion. [38][39][40] Figure 6 shows the room temperature Raman spectra of the glassy samples with varying TiO 2 contents.…”
Section: Samplementioning
confidence: 72%
“…Non-linear fitting of SiO 2 content in both slags through Origin software is shown in Figure 10 of the crystalline phase. The crystals tended to be more faceted and anisotropic when their Jackson α factor increased [20]. The main crystalline phases and their corresponding melting temperature and Jackson α factors were shown in Table 3.…”
Section: Kinetics Equilibrium Model Of Slag During the Reactionmentioning
confidence: 99%
“…Many attempts based on conventional slag still find it difficult to avoid the slag-steel reaction effectively. Therefore, some researchers began to explore the study of non-reactive or weakly reactive slag [6,[14][15][16][17][18][19][20][21]. Among them, Wang et al [16,17] studied the effect of various oxide additions on the crystallization behavior and heat transfer properties of the CaO-Al 2 O 3 system continuous casting slag and provided some guidelines for the design of a reasonable CaO-Al 2 O 3 system slag.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, based on previous research, Jackson first established a theory to explain the solid–liquid interface morphology and proposed the Jackson α factor parameter to predict the metal crystal morphology . Guo et al introduced a thermodynamic method to estimate the Jackson α factor of a crystal in multicomponent mold fluxes, combining the previous findings and the FactSage thermodynamic database . The results revealed that CaF 2 , CaO · x Al 2 O 3 , CaO · y B 2 O 3 , and 3CaO · 2SiO 2 · CaF 2 precipitated in mold fluxes show different morphologies due to their different Jackson α factors and the precipitated crystals tend to be more faceted and anisotropic with increasing the Jackson α factors.…”
Section: Development Status Of Mold Fluxes For Continuous Casting Of mentioning
confidence: 99%